Research on Creep Characteristics and Influencing Factors of Cement Asphalt Composite Binder. (29th December 2020) - Li, Yimin; Yombah, Mulbah; Temitope, Ahmed Abdulakeem; Zou, Xiaolong; Yang, Fayong; Li, Wenbo; Jing, Hongjun
Abstract : Cement emulsified asphalt composite material (CA composite cement) has the excellent properties of cement and emulsified asphalt cement. As a composite cementing material, cement emulsified asphalt concrete can be one of the choices of road paving materials. However, under the effect of temperature and wheel load, the performance of it may get worse; especially, the creep behavior of CA composite cement has an important influence on the stability of pavement structure. This paper mainly focuses on the research on the creep and creep recovery performance of CA composite cement, determines the raw materials and proportions of CA composite cement, and formulates experimental research programs such as creep and creep recovery tests and stress scanning tests. The creep and creep recovery test research of CA composite cement was carried out, and the influence of creep and creep recovery characteristics, temperature, and A/C on the creep mechanical properties of CA composite cement was analyzed. The results show that the creep compliance of CA composite cement decreases with the increase of aging degree, the static mechanical properties tend to be elastic as a whole, and different factors such as temperature and A/C have different effects on the viscoelastic-plastic mechanical properties of the material.